An investigation on the role played by the internal audit function on the survival of banks in the Zimbabwean banking sector: a case study of ZB financial holdings. - Mutara, Kudzanai (Midlands State University, 2018)
This study focused on the role of Risk Based Internal Audit (RBIA) approach on assurance of enterprise wide risk management to ensure survival of banks in Zimbabwe a case study of ZBFHL. This enabled an investigation of the impact of Risk Based Internal Audit Approach on assurances of enterprise risk management to guarantee survival of banks in Zimbabwe. The research adopted a mixed research approach which used both qualitative and quantitative research with a view of getting information that explained the existing phenomena. The target population was 100 employees of ZBFHL and data was obtained from 71 of them. The study used stratified sampling technique in coming up with the samples Primary data was collected using questionnaires that were self-administered because of the quantitative aspect of the research and also interviews were used to gather data also because the study had a qualitative research. Quantitative data was analysed using the regression model. The study found a significant positive relationship between RBIA and bank survival. From the interviews the study found out that RBIA assurances provide guarantee of bank survival by ensuring good enterprise risks management processes, it was also discovered that RBIA faced challenges of lack of , resources and lack of risk appetite awareness affected the assurances through RBIA. The study recommended that management of ZBFHL should enhance the use of RBIA and ensure the audit function is fully funded to provide training to improve the skills required for the use of RBIA to improve assurances on enterprise risk management processes to guarantee bank survival.